Validated Culturally Responsive Science Assessment Using Integrated Content and Construct Analysis - Aisyah Ali; Singgih Bektiarso; Auldry Fransje Walukow; Erlia Narulita; Akhmad Kadir (Universitas Muhammadiyah Sidoarjo, 2025)
(General Background) The alignment of science assessment with students’ socio-cultural contexts is essential to ensure fairness and meaningful measurement of learning outcomes. (Specific Background) However, most contextualized assessments in science education emphasize content validity without empirically confirming their construct structure, limiting their interpretive strength. (Knowledge Gap) There remains a lack of studies that integrate content, empirical, and construct validity evidence in culturally responsive instruments, particularly those designed in parallel pre–post forms. (Aims) This study aimed to develop and validate an ethnoscience-based pre–post instrument by linking Aiken’s Content Validity Ratio (CVR, 4-point scale) with Confirmatory Factor Analysis (CFA, CR/AVE). (Results) Findings from five expert reviews showed 22 of 40 items exceeded the conservative threshold (Aiken’s V ≥ 0.80; CVR = 1.00). Field trials (N = 50) demonstrated moderate difficulty and positive discrimination, while CFA confirmed a three-factor structure with good fit (χ² = 34.203, df = 24, p = 0.083; CFI = 0.94; TLI = 0.92; RMSEA = 0.065). Composite reliability ranged from 0.718–0.797, and AVE was adequate for two factors (0.506; 0.568) and marginal for one (0.459). (Novelty) The study presents a transparent “content–empirical–construct” decision trail rarely reported in ethnoscience assessment. (Implications) This integrative validation framework demonstrates that cultural responsiveness and psychometric rigor can coexist, guiding fair and contextual science learning evaluations. Highlights: Integrates Aiken–CVR and CFA for comprehensive validity evidence. Confirms three-factor model with strong reliability and moderate AVE. Demonstrates synergy between cultural relevance and measurement rigor. Keywords: Content Validity, Confirmatory Factor Analysis, Ethnoscience, Culturally Responsive Assessment, Psychometric Validation